IMPLEMENTASI PELAYANAN ADMINISTRASI TERPADU KECAMATANDI KECAMATAN PANCORAN MAS KOTA DEPOK - Rahadian, Ahmad Hidayat; Saputra, Munir; Fauzi, M. (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2019)
This study was conducted to determine the factors that affect the performance of policy implementation, the factors that hinder the implementation of PATEN policy and performance assesment of service quality. This study uses a qualitative method of interviews, documentation and observation to describe and analyze the implementation of PATEN policy. The theory used is the Theory of Implementation Performance, George C Edwards III adnd Theory Inhibitors, Bambang Sunggono, Implementation and Quality Performance Assessment Theory, Zeithaml, V.A, Pasuraman and Berry.The result is a factor affecting performance of PATEN implementation is resources and position, while the inhibiting factor is the implementation of information, and performance assessment of service quality perceived by the public of the documents to be faster, efficient, effective and transparent. Based on the result of the analysis, the unavailability of online registration facilities and personnel are less responsive affect performance of PATEN implementation. Performance assessment of the quality of services by the public to be more rapid, efficient, effective and transparent. Local goverments need to provide a budget for the purpose of infrastructure and provide technical guidance to officers of PATEN excellent service. Kecamatan Pancoran Mas need to improve the quality of the apparatus. People are required to comply with the terms of the documents.